2016
DOI: 10.1177/1352458516679894
|View full text |Cite
|
Sign up to set email alerts
|

Hispanic Americans and African Americans with multiple sclerosis have more severe disease course than Caucasian Americans

Abstract: Whether disease course in Hispanic Americans (HA) with multiple sclerosis (MS) is different from Caucasian Americans (CA) or African Americans (AA) is unknown. We compared MS severity in the three main ethnic populations in our tertiary MS clinics using disease duration-adjusted rank score of disability: Patient-Derived Multiple Sclerosis Severity Score (P-MSSS). The age- and gender-adjusted P-MSSS was significantly higher in HA (3.9 ± 2.6) and AA (4.5 ± 3.0) compared to CA (3.4 ± 2.6; p < 0.0001 for both). Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
61
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(66 citation statements)
references
References 12 publications
3
61
0
2
Order By: Relevance
“…Among racial/ethnic subgroups, African Americans had the highest baseline severity scores, followed by Hispanic Americans, followed by white Americans, in agreement with our prior analyses. 18 Interestingly, no change in severity scores was observed for any of the subgroups of interest, including patients with relapses 3 months or more from the last visit. Patients with progressive disease showed a trend for worsening PMSSS with time.…”
Section: Discussionmentioning
confidence: 86%
“…Among racial/ethnic subgroups, African Americans had the highest baseline severity scores, followed by Hispanic Americans, followed by white Americans, in agreement with our prior analyses. 18 Interestingly, no change in severity scores was observed for any of the subgroups of interest, including patients with relapses 3 months or more from the last visit. Patients with progressive disease showed a trend for worsening PMSSS with time.…”
Section: Discussionmentioning
confidence: 86%
“…This data suggests that blacks have a higher mortality risk at a younger age than whites. It is possible that the clinical differences in MS reported in blacks compared to whites, where blacks are more commonly reported to have a malignant disease course including a more rapid accumulation of disability and increase central nervous system damage, would be influencing [25-29]. Using the North American Research Committee for MS registry, blacks were reported to have a slightly higher mortality rate than whites or other races, particularly at younger ages [17].…”
Section: Discussionmentioning
confidence: 99%
“…Our finding that higher proportions of NA and African ancestry increase the chance of presenting with MS at a younger age is of great interest as well. A recent study that compared Hispanics and African Americans to Whites ascertained in the Northeastern United States, with similar socioeconomic background, indicated that Hispanics have a younger age of onset compared to Whites and a similar age of onset to African Americans . Previous studies have also observed an even more pronounced age of onset difference between U.S. and non‐U.S.…”
Section: Discussionmentioning
confidence: 97%
“…An early study from Mexico reported ON as presenting symptom in 33%, a much higher proportion when compared to White historical cohorts . The observations that any deviation in the presentation and clinical progression of MS in Hispanics from Whites could be influenced by genetic admixture, until now, were simply speculative …”
Section: Discussionmentioning
confidence: 99%